A Case Study Of Multimedia University's Security Management - Arumugam, Kesavan A. (2005)
In this case study, the researcher had analyzed the Security Management System of the University in detail, as it practises a totally diffrent concept from the traditional local universities. For instance, 80% of the staffing operation of MMU Security Department is controlled by the outsourcing guards while other local universities usually have a very high proportion of its very own in-house guards.